Empowerment Community Welfare After the Pandemic in Indonesia: The Role of Fintech? - Asri Elies Alamanda (Fakultas Hukum, Universitas Internasional Batam, 2022)
Financial technology or fintech is a term or term to denote companies in the financial sector that provide modern technological innovations in banking payments. The number of financial technology is constantly increasing with various estimates and the number of more than ten thousand companies. The development of Financial Technology is inseparable from the risks, as some of the risks that arise are related to consumer protection which includes the protection of funds and user data. The purpose of this study is to find out how fintech regulation in Indonesia, to understand the existence of Fintech in the digital era and to know and understand the role of fintech in improving the welfare of society after the pandemic. The research method used is Normative Juridical and The approach method used is descriptive and qualitative research methods. The results showed that fintech is very popular and is an alternative to the use of financial technology and is a foundation for people who are far from the conventional financial business sector. OJK and BI as supervisors of the financial sector also issued several regulations related to the implementation of fintech in order to ensure a safe and comfortable financial business and not violate the principle of prudence. In its implementation, it is hoped that the public will not borrow and use fintech technology that has not been registered with the OJK or at BI. This requires the government to be more aggressive in socializing fintech that is legal and registered with the OJK or BI.